Pengujian Aplikasi KAI Access Menggunakan Black Box Testing Boundary Value Analysis (BVA) - Miftah Nur Rohman; Rahman Fauza; Denita Alhamdina Putri Arisandi; Nabila Desiana; Aliya Tazkiya Fajriyati; Chris Hendry Choong; Subhanjaya Angga Atmaja (Journal on Pustaka Cendekia Informatika, 2025)
This study aims to evaluate the functionality of the KAI Access application using Black Box Testing methods, specifically Boundary Value Analysis (BVA) and Graph-based Testing. The testing was conducted on key features such as registration, login, KAI Pay activation, and local ticket booking. The results indicate that while most features function as expected, there are notable issues—such as the lack of character limits in the email input field. This approach provides a comprehensive overview of the application's reliability and identifies areas that need improvement to enhance the quality of service.